KAPABILITAS DINAS LINGKUNGAN HIDUP KABUPATEN PELALAWAN DALAM PENGANGKUTAN SAMPAH DI KECAMATAN PANGKALAN KERINCI TAHUN 2022 - Alfi Chaniago; Wazni ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
In order to manage waste properly, the government has issued a policy on waste management with the issuance of Law Number 18 of 2008 concerning Implementation of Waste Management. To achieve Pangkalan Kerinci as the capital of Pelalawan Regency which is clean, healthy, comfortable, beautiful, and environmentally friendly, Pelalawan Regency Regional Regulation Number 7 of 2015 concerning Waste Management was issued as a follow-up to Law Number 18 of 2008. However, in implementing this policy, there are still problems, namely the irregular schedule of the operating garbage collection cars that transport waste from the waste source to the landfill resulting in the accumulation of waste . This study uses the capability theory of Kusumasari with the research method used is a qualitative method with a descriptive research type. The results of this study indicate that the capability of the Pelalawan Regency Environmental Service in transporting waste in Pangkalan Kerinci District in 2022 is still not optimal. There is only 1 indicator that is optimal, namely institutions that already have clear duties and functions based on applicable regulations. Meanwhile, the other 5 are inadequate human resources, human resources in waste transportation which ideally are 5 people, but there are only 4 people. Policy implementation in waste transportation that is not implemented properly, minimal financial conditions to buy additional garbage transportation fleets so that it runs optimally, technical waste transportation that is not optimal because it still leaves waste that cannot be transported all in one transport, and leadership that still needs new innovations in dealing with the issue of waste transportation to make it even better with the help of community participation in making waste transportation in Pangkalan Kerinci District more effective. Keywords : Government Capability, Garbage, Garbage Transportation